Food Processing: The Meat We Eat - Erica L. Bub; Keith Schneider; Chad Carr; Matt Hersom (EDIS)
Meat processing technology is used to produce many of the foods we enjoy, such as hot dogs, hamburgers, and chicken nuggets. Recently, the media has focused on certain meat products, giving them names such as “pink slime” and “meat glue.” The names of these products might have many people wondering what we are eating and how the meat we eat is produced. Part of being a good consumer is learning about what you eat, from how the food is made to whether the food is safe. This publication discusses the facts about meat processing so you can make knowledgeable decisions about the meat you eat. This 5-page fact sheet was written by Erica L. Bub, Keith Schneider, Chad Carr, and Matt Hersom, and published by the UF Department of Animal Sciences, December 2012.